IJCAI 2018 – Chinese Dominance Established - Gams, Matjaž (Informatica, 2018)
<span style="font-family: 'Times New Roman',serif; font-size: 9pt; mso-bidi-font-size: 10.0pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">IJCAI 2018 report.